The Contribution GPAN Community (Gerakan Perpustakaan Anak Nusantara) to Increase Public Interest in Reading - ASSA, Muhammad Assa Ridho Rousin; Galuh, Galuh Indah Zatadini (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to analyze the Lapak Baca activities organized by the Gerakan Perpustakaan Anak Nusantara (GPAN) Regional Tulungagung community in increasing the reading interest of visitors to Alun-Alun Tulungagung. Reading interest in Indonesia is relatively low, and initiatives such as Lapak Baca are an alternative to bring literacy closer to the community in a more inclusive way. This study uses a qualitative approach with a phenomenological method to explore the meaning of the experiences of volunteers and visitors to the activity. Data collection techniques include participant observation, structured interviews, and documentation. Informants consist of GPAN members and Lapak Baca visitors. The results of the study show that Lapak Baca activities create an inclusive space that encourages active community involvement in literacy activities. Children feel free to choose reading material, while volunteers feel they have an important role in educating the community. In addition, internal and external factors were found that influence reading interest, such as personal motivation, environmental support, and the availability of interesting reading materials. The obstacles faced include limited book collections and physical facilities of Lapak Baca. This study provides theoretical benefits in enriching community-based literacy studies as well as practical benefits as material for evaluating and developing the Lapak Baca program by GPAN and related parties. It is hoped that these results can be a reference for similar literacy initiatives in other areas.